Food Insecurity and Forgone Medical Care Among Cancer Survivors - McDougall, Jean A. (JCO Oncol Pract, 2020)
PURPOSE: Financial hardship is increasingly understood as a negative consequence of cancer and its treatment. As patients with cancer face financial challenges, they may be forced to make a trade-off between food and medical care. We characterized food insecurity and its relationship to treatment adherence in a population-based sample of cancer survivors. METHODS: Individuals 21 to 64 years old, diagnosed between 2008 and 2016 with stage I-III breast, colorectal, or prostate cancer were identified from the New Mexico Tumor Registry and invited to complete a survey, recalling their financial experience in the year before and the year after cancer diagnosis. Multivariable logistic regression was used to estimate odds ratios (ORs) and 95%CIs. RESULTS: Among 394 cancer survivors, 229 (58%) were food secure in both the year before and the year after cancer diagnosis (persistently food secure), 38 (10%) were food secure in the year before and food insecure in the year after diagnosis (newly food insecure), and 101 (26%) were food insecure at both times (persistently food insecure). Newly food-insecure (OR, 2.82; 95% CI, 1.02 to 7.79) and persistently food-insecure (OR, 3.04; 95% CI,1.36 to 6.77) cancer survivors were considerably more likely to forgo, delay, or make changes to prescription medication than persistently food-secure survivors. In addition, compared with persistently food-secure cancer survivors, newly food-insecure (OR, 9.23; 95% CI, 2.90 to 29.3), and persistently food-insecure (OR, 9.93; 95% CI, 3.53 to 27.9) cancer survivors were substantially more likely to forgo, delay, or make changes to treatment other than prescription medication. CONCLUSION: New and persistent food insecurity are negatively associated with treatment adherence. Efforts to screen for and address food insecurity among individuals undergoing cancer treatment should be investigated as a strategy to reduce socioeconomic disparities in cancer outcomes.